Carbon dioxide in-situ fixed hydrophobic membrane material and preparation method thereof

By introducing hydrophobic modification technology into the ceramic membrane material, the honeycomb membrane tube structure and nano micropores are formed, which solves the problem of the hydrophilicity of the surface of the ceramic membrane material limiting its application, and achieves an efficient in-situ fixation effect of carbon dioxide.

CN119746645AActive Publication Date: 2025-04-04CHINA PETROLEUM & CHEMICAL CORP +2

Patent Information

Application Number
CN202411876663.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-04
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing ceramic membrane materials are limited in their application in complex industrial waste gas treatment due to their surface hydrophilicity, especially in the in-situ fixation of carbon dioxide.

Method used

The ceramic membrane material is made of hydrophobic modified, with a hollow honeycomb membrane tube structure inside and a nanopore on the surface. The ceramic membrane tube is modified by a mixed solution (a solution of fluoride, anhydrous ethanol, boric acid and deionized water) to form an extremely strong hydrophobic layer.

Benefits of technology

The hydrophobicity of the membrane tube is improved, the contact area between the reaction liquid and carbon dioxide is increased, the reaction pressure of carbon dioxide is reduced, the mass transfer efficiency of carbon dioxide is improved, and the in-situ fixation rate of carbon dioxide is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746645A_ABST
    Figure CN119746645A_ABST
Patent Text Reader

Abstract

The invention provides a carbon dioxide in-situ fixed hydrophobic membrane material and a preparation method thereof. The surface of the prepared membrane material has rich nano-pore diameters, carbon dioxide can permeate into the membrane material, and the middle part of the hydrophobic ceramic membrane material is in a hollow honeycomb shape, and reaction liquid for fixing carbon dioxide in situ flows through the part. In the forming process of the porous hydrophobic ceramic membrane material, the porous hydrophobic ceramic membrane material is formed at a time through high-temperature firing, and the yield is high; and then the ceramic membrane material is brushed with a hydrophobic material and then subjected to secondary low-temperature firing, so that the surface of the ceramic membrane material has extremely high hydrophobicity, and the hydrophobicity of the ceramic membrane tube is hardly changed after the ceramic membrane tube is used for multiple times. The method has the advantages that the method is novel and easy to implement, secondary low-temperature firing is carried out on the basis of a hydrophilic ceramic membrane material at the beginning to achieve hydrophobic modification, the air pressure needed when gas enters a membrane tube is reduced, and the mass transfer efficiency of the membrane tube is enhanced; the service life of the membrane tube is prolonged, and the use cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of hydrophobic ceramic membrane materials, and in particular to a hydrophobic ceramic membrane material for in-situ fixation of carbon dioxide in complex industrial waste gas and a preparation method thereof. Background Art

[0003] Membrane separation technology is an efficient way to control pollution, with many advantages such as easy operation, low cost, energy-saving processing, and system installation. According to material classification, membranes can be divided into organic polymer membranes and inorganic ceramic membranes. Organic polymer membranes have a high market share due to their abundant manufacturing materials, easy pore size control, and high packing density of membrane components. However, organic polymer membranes are similar to most organic pollutants in chemical structure characteristics, are easily contaminated by organic liquids, and have low thermal stability and mechanical strength, resulting in a short service life. Inorganic ceramic membranes have been widely studied in recent years due to their significant advantages such as high mechanical strength, good thermal stability and chemical stability. However, ceramic materials are usually hydrophilic due to the influence of surface hydroxyl groups, which will limit the application scope of porous ceramic membranes, such as membrane distillation, waste gas treatment and oil-water separation.

[0004] At present, the main methods used for hydrophobic modification of ceramic membranes include surface coating, surface spraying, surface chemical polymerization, surface grafting polymerization, surface radiation grafting, vacuum surface coating plasma surface polymerization and other means. Among them, the solution grafting polymerization method uses the presence of hydroxyl groups (-OH) on the surface of the ceramic membrane and selects fluorine-containing, chlorine-containing or amino-containing organic silane as a modifier. The organic silane is covalently linked to the substrate through a grafting polymerization reaction to obtain a composite membrane. This modification method is simple and easy, can be implemented in any laboratory, and can obtain a high-performance hydrophobic microporous membrane that can be used in the membrane distillation process. At the same time, it also retains the advantages of the ceramic membrane itself, such as high mechanical strength and narrow pore size distribution. Summary of the invention

[0005] The main purpose of the present invention is to provide a hydrophobic ceramic membrane material and a preparation method thereof for in-situ fixation of carbon dioxide in complex industrial waste gas, which can effectively solve the problem of large amounts of carbon oxide emissions caused by coal combustion and efficiently fix carbon dioxide in the atmosphere in-situ.

[0006] The technical solution adopted by the present invention is: a hydrophobic membrane material for in-situ fixation of carbon dioxide, characterized in that the hydrophobic membrane material is a hydrophobically modified ceramic membrane material, the interior of which is a hollow honeycomb membrane tube structure, the surface has nanopores, and the diameter of the pores is 50-200nm; the honeycomb membrane tube ceramic entity has nanopores inside, and the pores are closely connected; after the ceramic membrane tube is hydrophobically modified, its internal structure becomes smooth from rough, the entire membrane tube has strong hydrophobicity, and the contact angle reaches 130°-165°.

[0007] The present invention also provides a method for preparing the carbon dioxide in-situ fixation hydrophobic membrane material, the preparation process of which is as follows: (1) Screen the required raw materials through a sieve, mix them according to the proportion, and then pour them all into a V-type mixer for centralized mixing; (2) Adding PVA solution and deionized water to the material obtained in step (1), and stirring in a double-shaft mixer to obtain a dry pressed blank; (3) After the dry pressed blank is cooled, isostatic pressing is performed in a honeycomb mold to obtain a membrane tube blank; (4) De-membraning and drying the membrane tube embryo obtained in step (3); (5) placing the membrane tube embryo obtained in step (4) into a firing boat, and filling the gap between the membrane tube embryo and the firing boat with high-purity zirconium oxide sand; (6) placing the membrane tube blank and the firing boat of step (5) in a kiln to fire to obtain a ceramic membrane material; (7) The pH of the ceramic membrane material obtained in (6) is adjusted to neutral, washed and dried, and then immersed in the modified solution for 3-5 times. After each immersion, the ceramic membrane tube is placed in an oven and baked for 30 min-60 min. After the last baking, the ceramic membrane tube is placed in a low-temperature kiln and fired at a rate of 0.5-1.5°C / min to 250-280°C, and maintained at the highest temperature for 2-3 hours. The hydrophobic ceramic membrane material is then cooled to room temperature to obtain the hydrophobic ceramic membrane material.

[0008] Furthermore, in the step (1), the raw materials used are 75-77wt% of silicon carbide powder, 2-3wt% of powdered coal ash, 3-4wt% of silicon powder, 1-3wt% of dextrin, 2-5wt% of carboxymethyl cellulose, 5-6wt% of kaolin, and 0.1-0.4wt% of tetraethylethylenediamine.

[0009] Furthermore, in the step (1), the sieved particle size is 200-500 mesh, and the intensive mixing is carried out in a V-type mixer for 3-5 hours.

[0010] Furthermore, in the step (2), 5-8 wt % of PVA solution is added; and the mixture is stirred in a twin-shaft mixer for 3-5 hours.

[0011] Furthermore, in the step (3), the dry pressed blank is isostatically pressed in a honeycomb mold at a pressure of 35-50 MPa to obtain a membrane tube blank.

[0012] Furthermore, in the step (4), the membrane tube embryo is demolded and then dried in a drying oven at 60-90° C. for 16-24 hours.

[0013] Furthermore, in step (6), the membrane tube blank and the firing boat are placed in a kiln, heated to 1200-1250°C at a rate of 0.5-1.5°C / min, and kept at the highest temperature for 4-6 hours, and then cooled to room temperature to obtain a ceramic membrane material.

[0014] Furthermore, in step (7), the modified solution used is prepared by mixing carbon fluoride, anhydrous ethanol, boric acid and deionized water in a mass ratio of 1:100-1:200.

[0015] Furthermore, the modified solution comprises carbon fluoride, anhydrous ethanol and boric acid in a mass ratio of: carbon fluoride (10-20%), anhydrous ethanol (30-40%) and boric acid (40-60%).

[0016] The carbon dioxide in-situ fixation hydrophobic membrane material provided by the present invention can be used for in-situ fixation of carbon dioxide in complex industrial waste gas. When carbon dioxide enters the membrane tube for reaction, the pressure inside the entire device is 0.01-0.05MPa.

[0017] In the present invention, dextrin is used as a pore agent and carboxymethyl cellulose is used as an organic binder in the added raw materials. The gap between the membrane tube embryo and the sintering boat is filled with high-purity zirconium oxide sand to prevent the ceramic membrane material from expanding during the sintering process, resulting in the substandard quality of the ceramic membrane material production product.

[0018] The modified solution used in the present invention is prepared by mixing carbon fluoride, anhydrous ethanol, boric acid and deionized water in a certain proportion. The modification process of the membrane tube is essentially to perform secondary firing on the ceramic membrane tube so that a very strong hydrophobic layer is formed on its surface. After the ceramic membrane tube is modified by the modified solution, its internal structure changes from rough to smooth, and the entire membrane tube has strong hydrophobicity. The membrane tube is modified to form a hydrophobic layer, and the hydrophobic performance of the membrane tube will not be greatly reduced after it is used multiple times.

[0019] The carbon dioxide in-situ fixation hydrophobic membrane material provided by the present invention has micropores inside the membrane tube that become smooth from rough after hydrophobic modification, and the contact angle of the entire membrane tube surface becomes 130°-165°; when carbon dioxide is in-situ fixed in the membrane tube, the contact area between the reaction liquid and the carbon dioxide can be greatly increased, the gas pressure of carbon dioxide entering the membrane tube is reduced to 0.01-0.05MPa, and the mass transfer efficiency of carbon dioxide is improved at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The figure is a schematic diagram of the process of the preparation method according to the embodiment of the present invention.

[0021] Figure 2This is a comparison chart of the contact angles of modified and unmodified ceramic membrane tubes in implementation case 1; a is the unmodified ceramic membrane tube, and b is the modified ceramic membrane tube.

[0022] Figure 3 This is a comparison of the surface microstructures of the modified and unmodified ceramic membrane tubes in Example 1; a is the unmodified ceramic membrane tube, and b is the modified ceramic membrane tube. DETAILED DESCRIPTION

[0023] The present invention will be further described in detail below through specific embodiments in conjunction with the accompanying drawings. However, it is necessary to point out that the following embodiments are only used to describe the content of the invention and do not constitute a limitation on the protection scope of the present invention.

[0024] The preparation process of the hydrophobically modified ceramic membrane material in the following embodiments is shown in the attached Figure 1 For a comparison of the contact angles of modified and unmodified ceramic membrane tubes, see Attachment Figure 2 . Conceptual description of relevant test indicators in the embodiment:

[0025] Contact angle: The contact angle is an important parameter that describes the interaction between a liquid and a solid surface. Specifically, the contact angle is the angle between a stationary droplet of liquid on a solid surface and the surface. This angle is represented by the angle between the tangent line at the interface of the liquid, solid and gas phases and the solid surface.

[0026] Test method: 1. Place the solid sample on the sample table; 2. Use a syringe to drop a drop of liquid on the solid surface; 3. Use a camera to capture a side image of the drop on the solid surface; 4. Use image analysis software to calculate the angle between the drop and the solid surface.

[0027] CO2 in-situ fixation rate: the ratio of CO2 absorbed after entering the reaction device.

[0028]

[0029] x: CO2 in situ fixation rate; b: CO2 reaction amount; a: CO2 intake amount. Example 1

[0030] The raw materials used to prepare the ceramic membrane material are sieved with a 200-mesh sieve, and then mixed in a V-type mixer for 3-5 hours in a proportion of 75-77wt% of silicon carbide powder, 2-3wt% of powdered fly ash, 3-4wt% of silicon micropowder, 1wt% of dextrin, 2wt% of carboxymethyl cellulose, 5-6wt% of kaolin, and 0.1-0.4wt% of tetraethylethylenediamine. Then, 5-8wt% of PVA solution is added and stirred in a twin-shaft mixer for 3-5 hours.

[0031] The dry pressed blank prepared in the double-shaft mixer is poured into a honeycomb mold prepared in advance and then pressed. A honeycomb membrane tube embryo is statically pressed under a pressure of 45 MPa, and then demolded and placed in a drying oven at 90°C for 24 hours. After drying, the membrane tube embryo is placed in a firing boat for sintering. The gap between the firing boat and the membrane tube embryo is filled with high-purity zirconia. The purpose of filling is to prevent the membrane tube from expanding and cracking during the sintering process. When the membrane tube embryo and the firing boat are placed in a kiln for sintering, the temperature is gradually increased at a rate of 1°C / min to 1200-1250°C. When the temperature reaches this temperature range, the temperature is maintained for 4 hours, and then cooled to room temperature and demolded to obtain a ceramic membrane material with a nano-micropore diameter of about 200 nm on its surface.

[0032] The sintered ceramic membrane material is first soaked in a 1-2 mol / L NaOH solution for 30-60 min, then rinsed with distilled water for a period of time until the pH of the ceramic membrane material becomes neutral, and then the membrane tube is placed in an oven for drying; the dried ceramic membrane material is soaked in a modified solution for 3-5 times, and after each soaking, it is placed in an oven for baking for 30-60 min. After baking for the last time, the ceramic membrane tube is placed in a low-temperature kiln for firing, and the temperature is increased to 250-280°C at a rate of 0.5-1.5°C / min, and the highest temperature is kept constant for 2-3 h, and the hydrophobic ceramic membrane material is obtained by cooling with the furnace to room temperature. The modified solution is a mixture of carbon fluoride, anhydrous ethanol, boric acid (the mass ratio of the three is 10:30:60) and deionized water in a mass ratio of 1:200 between the solution of each substance and the ionized water.

[0033] The modified ceramic membrane material has nano-micropores inside the body, and the micropores are closely connected. The contact angle is measured to be about 138°. When used for in-situ fixation of carbon dioxide in complex industrial waste gas, the reaction pressure is about 0.05MPa, and the in-situ fixation rate of carbon dioxide is 97.1%. The results of the unmodified ceramic membrane material are compared in Table 1. The contact angle comparison is shown in the figure below. Figure 2 shown.

[0034] In order to further analyze the changes in the microstructure of the ceramic membrane tube caused by the modified solution, we conducted a contact angle test on the membrane tube. Figure 3 The following is a comparison of the surface microstructures of modified and unmodified ceramic membrane tubes; a is the unmodified ceramic membrane tube, and b is the modified ceramic membrane tube; it can be seen from the figure that the surface structure of the modified ceramic membrane tube has become significantly smoother, and its contact angle has also become significantly larger after testing, and the hydrophobicity has been significantly enhanced.

[0035] Table 1 . Example 2

[0036] The raw materials used to prepare the ceramic membrane material are sieved with a 200-mesh sieve, and then mixed in a V-type mixer for 3-5 hours in a proportion of 75-77wt% of silicon carbide powder, 2-3wt% of powdered fly ash, 3-4wt% of silicon micropowder, 1wt% of dextrin, 3wt% of carboxymethyl cellulose, 5-6wt% of kaolin, and 0.1-0.4wt% of tetraethylethylenediamine. Then, 5-8wt% of PVA solution is added and stirred in a twin-shaft mixer for 3-5 hours.

[0037] The dry pressed blank prepared in the double-shaft mixer is poured into a honeycomb mold prepared in advance and then pressed. A honeycomb membrane tube embryo is formed by static pressing at a pressure of 45 MPa, and then demolding is performed and the embryo is placed in a drying oven at 90°C for 24 hours. After drying, the membrane tube embryo is placed in a firing boat for sintering. The gap between the firing boat and the membrane tube embryo is filled with high-purity zirconia. The purpose of filling is to prevent the membrane tube from expanding and cracking during the sintering process. When the membrane tube embryo and the firing boat are placed in a kiln for sintering, the temperature is gradually increased at a rate of 1°C / min to 1200-1250°C. When the temperature reaches this temperature range, the temperature is maintained for 4 hours, and then cooled to room temperature and demolded to obtain a ceramic membrane material with a nano-micropore diameter of about 160 nm on its surface.

[0038] The sintered ceramic membrane material is first soaked in a 1-2 mol / L NaOH solution for 30-60 min, then rinsed with distilled water for a period of time until the pH of the ceramic membrane material becomes neutral, and then the membrane tube is placed in an oven for drying; the dried ceramic membrane material is soaked in a modified solution for 3-5 times, and after each soaking, it is placed in an oven for baking for 30-60 min. After baking for the last time, the ceramic membrane tube is placed in a low-temperature kiln for firing, and the temperature is increased to 250-280°C at a rate of 0.5-1.5°C / min, and the highest temperature is maintained at a constant temperature for 2-3 h, and the hydrophobic ceramic membrane material is obtained by cooling with the furnace to room temperature. The modified solution is a mixture of carbon fluoride, anhydrous ethanol, boric acid (the mass ratio of the three is 20:40:40) and deionized water in a mass ratio of 1:200 between the solution of each substance and the ionized water.

[0039] The modified ceramic membrane material has nano-pores inside the body, and the pores are closely connected. The contact angle is measured to be about 146.6°. When used for in-situ fixation of carbon dioxide in complex industrial waste gas, the reaction pressure is about 0.047 MPa, and the in-situ fixation rate of carbon dioxide is 98.5%. The comparison of the results with the unmodified ceramic membrane material is shown in Table 2.

[0040] Table 2 . Example 3

[0041] The raw materials used to prepare the ceramic membrane material are sieved with a 400-mesh sieve, and then mixed in a V-type mixer for 3-5 hours according to the ratio of 75-77wt% of silicon carbide powder, 2-3wt% of powdered fly ash, 3-4wt% of silicon powder, 2wt% of dextrin, 3.5wt% of carboxymethyl cellulose, 5-6wt% of kaolin, and 0.1-0.4wt% of tetraethylethylenediamine, and then 5-8wt% of PVA solution is added and stirred in a double-shaft mixer for 3-5 hours; The dry pressed blank prepared in the double-shaft mixer is poured into a honeycomb mold prepared in advance and then pressed. A honeycomb membrane tube embryo is statically pressed under a pressure of 45 MPa, and then demolded and placed in a drying oven at 90°C for 24 hours. After drying, the membrane tube embryo is placed in a firing boat for sintering. The gap between the firing boat and the membrane tube embryo is filled with high-purity zirconia. The purpose of filling is to prevent the membrane tube from expanding and cracking during the sintering process. When the membrane tube embryo and the firing boat are placed in a kiln for sintering, the temperature is gradually increased at a rate of 1°C / min to 1200-1250°C. When the temperature reaches this temperature range, this temperature is maintained for 4 hours, and then cooled to room temperature and demolded to obtain a ceramic membrane material with a nano-micropore diameter of about 110 nm on its surface.

[0042] The sintered ceramic membrane material is first soaked in a 1-2 mol / L NaOH solution for 30-60 min, then rinsed with distilled water for a period of time until the pH of the ceramic membrane material becomes neutral, and then the membrane tube is placed in an oven for drying; the dried ceramic membrane material is soaked in a modified solution for 3-5 times, and after each soaking, it is placed in an oven for baking for 30-60 min. After baking for the last time, the ceramic membrane tube is placed in a low-temperature kiln for firing, and the temperature is increased to 250-280°C at a rate of 0.5-1.5°C / min, and the highest temperature is maintained at a constant temperature for 2-3 h, and the hydrophobic ceramic membrane material is obtained by cooling with the furnace to room temperature. The modified solution is a mixture of carbon fluoride, anhydrous ethanol, boric acid (the mass ratio of the three is 15:35:50) and deionized water in a mass ratio of 1:150 between the solution of each substance and the ionized water.

[0043] The modified ceramic membrane material has nano-pores inside the body, and the pores are closely connected. The contact angle is measured to be about 153.2°. When used for in-situ fixation of carbon dioxide in complex industrial waste gas, the reaction pressure is about 0.03 MPa, and the in-situ fixation rate of carbon dioxide is 98.9%. The comparison of the results with the unmodified ceramic membrane material is shown in Table 3.

[0044] Table 3 . Example 4

[0045] The raw materials used to prepare the ceramic membrane material are sieved with a 400-mesh sieve, and then mixed in a V-type mixer for 3-5 hours in a proportion of 75-77wt% of silicon carbide powder, 2-3wt% of powdered fly ash, 3-4wt% of silicon micropowder, 2wt% of dextrin, 4wt% of carboxymethyl cellulose, 5-6wt% of kaolin, and 0.1-0.4wt% of tetraethylethylenediamine. Then, 5-8wt% of PVA solution is added and stirred in a twin-shaft mixer for 3-5 hours.

[0046] The dry pressed blank prepared in the double-shaft mixer is poured into a honeycomb mold prepared in advance and then pressed. A honeycomb membrane tube embryo is formed by static pressing at a pressure of 45 MPa, and then demolding is performed and the embryo is placed in a drying oven at 90°C for 24 hours. After drying, the membrane tube embryo is placed in a firing boat for sintering. The gap between the firing boat and the membrane tube embryo is filled with high-purity zirconia. The purpose of filling is to prevent the membrane tube from expanding and cracking during the sintering process. When the membrane tube embryo and the firing boat are placed in a kiln for sintering, the temperature is gradually increased at a rate of 1°C / min to 1200-1250°C. When the temperature reaches this temperature range, the temperature is maintained for 4 hours, and then cooled to room temperature and demolded to obtain a ceramic membrane material with a nano-micropore diameter of about 80 nm on its surface.

[0047] The sintered ceramic membrane material is first soaked in a 1-2 mol / L NaOH solution for 30-60 min, then rinsed with distilled water for a period of time until the pH of the ceramic membrane material becomes neutral, and then the membrane tube is placed in an oven for drying; the dried ceramic membrane material is soaked in a modified solution for 3-5 times, and after each soaking, it is placed in an oven for baking for 30-60 min. After baking for the last time, the ceramic membrane tube is placed in a low-temperature kiln for firing, and the temperature is increased to 250-280°C at a rate of 0.5-1.5°C / min, and the highest temperature is maintained at a constant temperature for 2-3 h, and the hydrophobic ceramic membrane material is obtained by cooling with the furnace to room temperature. The modified solution is a mixture of carbon fluoride, anhydrous ethanol, boric acid (the mass ratio of the three is 10:40:50) and deionized water in a mass ratio of 1:150 between the solution of each substance and the ionized water.

[0048] The modified ceramic membrane material has nano-pores inside the body, and the pores are closely connected. The contact angle is measured to be about 156.2°. When used for in-situ fixation of carbon dioxide in complex industrial waste gas, the reaction pressure is about 0.021 MPa, and the in-situ fixation rate of carbon dioxide is 98.9%. The comparison of the results with the unmodified ceramic membrane material is shown in Table 4.

[0049] Table 4 . Example 5

[0050] The raw materials used to prepare the ceramic membrane material are sieved with a 500-mesh sieve, and then mixed in a V-type mixer for 3-5 hours in a proportion of 75-77wt% of silicon carbide powder, 2-3wt% of powdered fly ash, 3-4wt% of silicon micropowder, 3wt% of dextrin, 4wt% of carboxymethyl cellulose, 5-6wt% of kaolin, and 0.1-0.4wt% of tetraethylethylenediamine. Then, 5-8wt% of PVA solution is added and stirred in a twin-shaft mixer for 3-5 hours.

[0051] The dry pressed blank prepared in the double-shaft mixer is poured into a honeycomb mold prepared in advance and then pressed. A honeycomb membrane tube embryo is statically pressed under a pressure of 45 MPa, and then demolded and placed in a drying oven at 90°C for 24 hours. After drying, the membrane tube embryo is placed in a firing boat for sintering. The gap between the firing boat and the membrane tube embryo is filled with high-purity zirconia. The purpose of filling is to prevent the membrane tube from expanding and cracking during the sintering process. When the membrane tube embryo and the firing boat are placed in a kiln for sintering, the temperature is gradually increased at a rate of 1°C / min to 1200-1250°C. When the temperature reaches this temperature range, this temperature is maintained for 4 hours, and then cooled to room temperature and demolded to obtain a ceramic membrane material with a nano-micropore diameter of about 60 nm on its surface.

[0052] The sintered ceramic membrane material is first soaked in a 1-2 mol / L NaOH solution for 30-60 min, then rinsed with distilled water for a period of time until the pH of the ceramic membrane material becomes neutral, and then the membrane tube is placed in an oven for drying; the dried ceramic membrane material is soaked in a modified solution for 3-5 times, and after each soaking, it is placed in an oven for baking for 30-60 min. After baking for the last time, the ceramic membrane tube is placed in a low-temperature kiln for firing, and the temperature is increased to 250-280°C at a rate of 0.5-1.5°C / min, and the highest temperature is maintained at a constant temperature for 2-3 h, and the hydrophobic ceramic membrane material is obtained by cooling with the furnace to room temperature. The modified solution is a mixture of carbon fluoride, anhydrous ethanol, boric acid (the mass ratio of the three is 15:40:45) and deionized water in a mass ratio of 1:100 between the solution of each substance and the ionized water.

[0053] The modified ceramic membrane material has nano-pores inside the body, and the pores are closely connected. The contact angle is measured to be about 158.1°. When used for in-situ fixation of carbon dioxide in complex industrial waste gas, the reaction pressure is about 0.015 MPa, and the in-situ fixation rate of carbon dioxide is 99.2%. The comparison of the results with the unmodified ceramic membrane material is shown in Table 5.

[0054] Table 5 . Example 6

[0055] The raw materials used to prepare the ceramic membrane material are sieved with a 500-mesh sieve, and then mixed in a V-type mixer for 3-5 hours in a proportion of 75-77wt% of silicon carbide powder, 2-3wt% of powdered fly ash, 3-4wt% of silicon micropowder, 3wt% of dextrin, 5wt% of carboxymethyl cellulose, 5-6wt% of kaolin, and 0.1-0.4wt% of tetraethylethylenediamine. Then, 5-8wt% of PVA solution is added and stirred in a twin-shaft mixer for 3-5 hours.

[0056] The dry pressed blank prepared in the double-shaft mixer is poured into a honeycomb mold prepared in advance and then pressed. A honeycomb membrane tube embryo is statically pressed under a pressure of 45 MPa, and then demolded and placed in a drying oven at 90°C for 24 hours. After drying, the membrane tube embryo is placed in a firing boat for sintering. The gap between the firing boat and the membrane tube embryo is filled with high-purity zirconia. The purpose of filling is to prevent the membrane tube from expanding and cracking during the sintering process. When the membrane tube embryo and the firing boat are placed in a kiln for sintering, the temperature is gradually increased at a rate of 1°C / min to 1200-1250°C. When the temperature reaches this temperature range, it is maintained at this temperature for 4 hours, then cooled to room temperature and demolded to obtain a ceramic membrane material with a nano-micropore diameter of about 50 nm on its surface.

[0057] The sintered ceramic membrane material is first soaked in a 1-2 mol / L NaOH solution for 30-60 min, then rinsed with distilled water for a period of time until the pH of the ceramic membrane material becomes neutral, and then the membrane tube is placed in an oven for drying; the dried ceramic membrane material is soaked in a modified solution for 3-5 times, and after each soaking, it is placed in an oven for baking for 30-60 min. After baking for the last time, the ceramic membrane tube is placed in a low-temperature kiln for firing, and the temperature is increased to 250-280°C at a rate of 0.5-1.5°C / min, and the highest temperature is maintained at a constant temperature for 2-3 h, and the hydrophobic ceramic membrane material is obtained by cooling with the furnace to room temperature. The modified solution is a mixture of carbon fluoride, anhydrous ethanol, boric acid and deionized water in a mass ratio of 1:100 between the solution of each substance and the ionized water.

[0058] The modified ceramic membrane material has nano-pores inside the body, and the pores are closely connected. The contact angle is measured to be about 159.6°. When used for in-situ fixation of carbon dioxide in complex industrial waste gas, the reaction pressure is about 0.01 MPa, and the in-situ fixation rate of carbon dioxide is 99.2%. The comparison of the results with the unmodified ceramic membrane material is shown in Table 6.

[0059] Table 6 .

[0060] According to the comparison of different implementation cases, it can be seen that the beneficial results of the present invention are: 1. After hydrophobic modification, the contact angle of the entire membrane tube surface is greatly increased. When carbon dioxide is fixed in situ in the membrane tube, the contact area between the reaction liquid and carbon dioxide can be greatly increased, the reaction pressure of carbon dioxide is reduced, and the mass transfer efficiency of carbon dioxide is improved; 2. As the particle size of the raw material screening decreases and the content of dextrin and carboxymethyl cellulose increases, the nanopore size on the surface and inside of the ceramic membrane tube becomes smaller; 3. Gradually increasing the mass mixing ratio of carbon fluoride, anhydrous ethanol, boric acid and deionized water in the modified solution helps to increase the hydrophobicity of the modified ceramic membrane tube, reduce the pressure during the reaction, and at the same time improve the in-situ fixation rate of the CO2 reaction, thereby extending the service life of the membrane tube and reducing the cost of use.

Claims

1. A hydrophobic membrane material for in-situ fixation of carbon dioxide, characterized in that The hydrophobic membrane material is a hydrophobically modified ceramic membrane material, which has a hollow honeycomb membrane tube structure inside and nanopores on the surface with a pore diameter of 50-200nm; the honeycomb membrane tube ceramic entity has nanopores inside, and the pores are closely connected; after the ceramic membrane tube is hydrophobically modified, its internal structure changes from rough to smooth, the entire membrane tube has strong hydrophobicity, and the contact angle reaches 130°-165°.

2. The method for preparing a hydrophobic membrane material for in-situ fixation of carbon dioxide according to claim 1, characterized in that: The preparation process is: (1) The required raw materials are sieved through a sieve, mixed according to the proportion, and then poured into a V-type mixer for centralized mixing; (2) Adding PVA solution and deionized water to the material obtained in step (1), and stirring in a double-shaft mixer to obtain a dry pressed blank; (3) After the dry pressed blank is cooled, isostatic pressing is performed in a honeycomb mold to obtain a membrane tube blank; (4) De-membraning and drying the membrane tube embryo obtained in step (3); (5) placing the membrane tube embryo obtained in step (4) into a firing boat, and filling the gap between the membrane tube embryo and the firing boat with high-purity zirconium oxide sand; (6) placing the membrane tube blank and the firing boat of step (5) in a kiln to fire to obtain a ceramic membrane material; (7) The pH of the ceramic membrane material obtained in (6) is adjusted to neutral, washed and dried, and then immersed in the modified solution for 3-5 times. After each immersion, the ceramic membrane tube is placed in an oven and baked for 30 min-60 min. After the last baking, the ceramic membrane tube is placed in a low-temperature kiln and fired at a rate of 0.5-1.5°C / min to 250-280°C, and maintained at the highest temperature for 2-3 hours. The hydrophobic ceramic membrane material is then cooled to room temperature to obtain the hydrophobic ceramic membrane material.

3. The method for preparing a hydrophobic membrane material for in-situ fixation of carbon dioxide according to claim 2, characterized in that: In step (1), the raw materials used are 75-77wt% of silicon carbide powder, 2-3wt% of powdered coal ash, 3-4wt% of silicon powder, 1-3wt% of dextrin, 2-5wt% of carboxymethyl cellulose, 5-6wt% of kaolin, and 0.1-0.4wt% of tetraethylethylenediamine.

4. The method for preparing a hydrophobic membrane material for in-situ fixation of carbon dioxide according to claim 2, characterized in that: In step (1), the sieved particle size is 200-500 mesh, and the mixture is mixed intensively in a V-type mixer for 3-5 hours.

5. The method for preparing a hydrophobic membrane material for in-situ fixation of carbon dioxide according to claim 2, characterized in that: In step (2), 5-8 wt % of PVA solution is added; and the mixture is stirred in a twin-shaft mixer for 3-5 hours.

6. The method for preparing a hydrophobic membrane material for in-situ fixation of carbon dioxide according to claim 2, characterized in that: In step (3), the dry pressed blank is isostatically pressed in a honeycomb mold at a pressure of 35-50 MPa to obtain a membrane tube blank.

7. The method for preparing a hydrophobic membrane material for in-situ fixation of carbon dioxide according to claim 2, characterized in that: In step (4), the membrane tube embryo is de-membraned and then dried in a drying oven at 60-90° C. for 16-24 hours.

8. The method for preparing a hydrophobic membrane material for in-situ fixation of carbon dioxide according to claim 2, characterized in that: In step (6), the membrane tube blank and the firing boat are placed in a kiln, and the temperature is raised to 1200-1250°C at a rate of 0.5-1.5°C / min, and the highest temperature is maintained at a constant temperature for 4-6 hours, and then cooled to room temperature to obtain a ceramic membrane material.

9. The method for preparing a hydrophobic membrane material for in-situ fixation of carbon dioxide according to claim 2, characterized in that: In step (7), the modified solution used is prepared by mixing carbon fluoride, anhydrous ethanol, boric acid and deionized water in a mass ratio of 1:100-1:

200.

10. The hydrophobic membrane material for in-situ fixation of carbon dioxide according to claim 1, characterized in that: Used for in-situ fixation of carbon dioxide in complex industrial waste gas. When carbon dioxide enters the membrane tube for reaction, the pressure inside the entire device is 0.01-0.05 MPa.

11. The hydrophobic membrane material for in-situ fixation of carbon dioxide according to claim 9, characterized in that: The modified solution comprises carbon fluoride, anhydrous ethanol and boric acid in the following mass ratios: carbon fluoride (10-20%), anhydrous ethanol (30-40%) and boric acid (40-60%).

Citation Information

Patent Citations

  • Method for preparing ceramic membrane at low temperature

    CN114573354A

  • Preparation method of zwitterion-fluorine functionalized anti-pollution polyamide composite membrane

    CN118788155A

  • Method of manufacturing hydrophobic and super-hydrophobic coating agent and coating method using the same

    KR1020170050320A

  • Hydrophobic, Self-Healing Coating and Coated Substrate, and Fabrication Method

    US20230399540A1

Cited By

  • Preparation method of fly ash-silane coupling agent composite ceramic membrane

    CN121244012A